Metal-Enhanced Fluorescence of Chlorophylls in Light-Harvesting Complexes Coupled to Silver Nanowires. (4th March 2013) - Kowalska, Dorota; Krajnik, Bartosz; Olejnik, Maria; Twardowska, Magdalena; Czechowski, Nikodem; Hofmann, Eckhard; Mackowski, Sebastian
Abstract : We investigate metal-enhanced fluorescence of peridinin-chlorophyll protein coupled to silver nanowires using optical microscopy combined with spectrally and time-resolved fluorescence techniques. In particular we study two different sample geometries: first, in which the light-harvesting complexes are deposited onto silver nanowires, and second, where solution of both nanostructures are mixed prior deposition on a substrate. The results indicate that for the peridinin-chlorophyll complexes placed in the vicinity of the silver nanowires we observe higher intensities of fluorescence emission as compared to the reference sample, where no nanowires are present. Enhancement factors estimated for the sample where the light-harvesting complexes are mixed together with the silver nanowires prior deposition on a substrate are generally larger in comparison to the other geometry of a hybrid nanostructure. While fluorescence spectra are identical both in terms of overall shape and maximum wavelength for peridinin-chlorophyll-protein complexes both isolated and coupled to metallic nanostructures, we conclude that interaction with plasmon excitations in the latter remains neutral to the functionality of the biological system. Fluorescence transients measured for the PCP complexes coupled to the silver nanowires indicate shortening of the fluorescence lifetime pointing towards modifications of radiative rate due to plasmonic interactions. Our results can be applied for developing ways to plasmonically control the light-harvesting capability of photosynthetic complexes.